Malignant Spinal Cord Compression Syndrome as an Initial Presentation of Testicular Cancer - Carlos Eduardo Salazar-Mejía; Edio Llerena-Hernández; David Hernández-Barajas; Oscar Vidal-Gutiérrez; Adriana González-Gutiérrez; Rolando Jacob Martínez-Granados; Blanca Otilia Wimer-Castillo (Case Reports in Oncological Medicine)
Malignant spinal cord compression syndrome (MSCCS) occurs in 2.5 to 5% of all oncological patients. In 20% of the cases, it is the initial manifestation. This syndrome is a rare event among germ cell tumors (GCT), occurring in only 1.7% of the patients. We present the case of a 24-year-old man who arrived at the emergency department with dysesthesia and paraparesis as well as urinary incontinence. Imaging studies showed an infiltrative lesion in the left testicle, pulmonary and hepatic metastatic disease, and a large retroperitoneal ganglionar conglomerate that infiltrated the spinal cord through the intervertebral foramina of the vertebra level T11 with displacement of the L1 vertebral body. A postoperative biopsy showed a pure embryonal carcinoma. In the initial approach of a young man who presents spinal cord compression, the presence of MSCCS associated with GCT should be considered as a possible cause. A high level of suspicion is required to achieve a timely diagnosis, to grant the patient the best possible outcome.